(Prze)grać w kości. Franz Mon: granice poezji, granice interpretacji - Kołodziej, Dorota (Przestrzenie Teorii, 2019)
This article attempts to discuss borders of interpretation in the light of concrete poetry. The paper compares Franz Mon’s pieces to earlier works, especially A throw of the dice will never abolish chance by Stephane Mallarme. This research is conducted in the context of Mon’s and Mallarme’s metapoetic commentary, who both show interest in the categories of playing and musical scores. The article attempts to transfer this perspective into an interpretation of four texts by Mon.